2013
DOI: 10.2478/hukin-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Game Indicators Determining Sports Performance in the NBA

Abstract: The main goal of the present study was to identify basketball game performance indicators which best determine sports level in the National Basketball Association (NBA) league. The research material consisted of all NBA game statistics at the turn of eight seasons (2003–11) and included 52 performance variables. Through detailed analysis the variables with high influence on game effectiveness were selected for final procedures. It has been proven that a limited number of factors, mostly offensive, determines s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 18 publications
2
41
0
3
Order By: Relevance
“…All participants were measured for selected body mass and body composition variables before and after the completion of a 12-week training period, which had been shown appropriate to observe changes in body composition (Lehnert et al, 2015; Mikołajec et al, 2013). Body mass and body composition were assessed by bioimpedance analysis (body’s inherent resistance to the electrical current) with the use of an electronic scale (Tanita TBF 300M).…”
Section: Methodsmentioning
confidence: 99%
“…All participants were measured for selected body mass and body composition variables before and after the completion of a 12-week training period, which had been shown appropriate to observe changes in body composition (Lehnert et al, 2015; Mikołajec et al, 2013). Body mass and body composition were assessed by bioimpedance analysis (body’s inherent resistance to the electrical current) with the use of an electronic scale (Tanita TBF 300M).…”
Section: Methodsmentioning
confidence: 99%
“…Studies on American basketball, to be precise on the most important league in the world the NBA, have found that the winning teams are characterised by better offensive efficiency, especially in the points scored in the third quarter, as well as standing out regarding fouls and steals (Mikołajec et al, 2013). In other leagues on the American continent, it has been shown that efficiency in throws, rebounds, steals and assists discriminate the winner from the losers in the Brazilian league (De Rose, 2004), or that in Chilean basketball many points are scored per possession (Fernández, Ortega, Ubal, Gómez, & Ibáñez, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In basketball, studies are frequently performed on the best professional leagues, the NBA or WNBA, at the top competitive level of professional leagues, as well as the World Championships. The NBA has been widely studied (García, Cañadas, & Antúnez, 2015;Ibáñez, García, Feu, Parejo, & Cañadas, 2009;Mikołajec, Maszczyk, & Zając, 2013;Ribeiro, Mukherjee, & Zeng, 2016). The best professional leagues using the FIBA regulations have also been studied, as the ACB (García, Saéz, Ibáñez, Parejo, & Cañadas, 2009;Puente, Coso, Salinero, & Abián-Vicén, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, relativamente aos jogos dos Playofs, o único preditor do sucesso das equipas encontrado foi a média de ressaltos defensivos por jogo. Consistente com os nossos resultados, estudos anteriores têm conirmado que as equipas vencedoras registam maiores eicácias de lançamento e maior número de ressaltos defensivos (Akers et (Mikotajec et al, 2013). Por outro lado, os resultados de um estudo com dados estatís-ticos da ACB (Liga Espanhola de Basquetebol) revelaram que, na fase regular, os indicadores assistências, ressaltos defensivos e lançamentos de 2pts e 3pts convertidos discriminam as equipas vencedoras das equipas derrotadas.…”
Section: Discussionunclassified